Implementing PBL In Human Computer Interaction Class - Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Bakar, Norasiken; Husain, Kalthom; Hasan, Hazmilah (2011)
Problem Based Learning (PBL) is increasingly used in many disciplines. PBL can be defined as a pedagogical strategy for posing significant, contextualized, real world situations, providing resources, guidance, instruction to learners as they develop content knowledge and problem solving skills. The purpose of this research is to evaluate effectiveness of students’ performances between self and peer assessment based on student’s preferences. The course entitled Human Computer Interaction (HCI) which constitutes a compulsory subject for students in the undergraduate Bachelor in Computer Science degree programmes. Three phases involved in this research methodology. Phase one is Analysis which includes literature survey and collection of preliminary analysis data. Second phase is Designing and Development which adopt ADDIE model as a basis for multimedia development. The last phase is Testing and Evaluation. There are three research instruments gathered to evaluate the project which are questionnaire, interview and prototype development. The prototype called PBLAssess is developed to support the effectiveness of teaching and learning. Findings of this study revealed that students prefer peer assessment than self assessment. The use of PBLAssess can increase student’s understanding towards the topic that has been taught. Results showed that assessment in PBL is significantly related to student’s performances and preferences.